Mobile Admission Process and Administrative Turnaround Time for Hospitalization of Outpatients: A Retrospective Study - Chung, Ho Sub; Namgung, Myeong; Bae, Sung Jin; Choi, Yunhyung; Lee, Dong Hoon; Kim, Chan Woong; Kim, Sunho; Jung, Kwang Yul (Applied Clinical Informatics, 2025)
This study compared the time efficiency of the hospital admission process using personal mobile devices to traditional walk-in methods, thereby assessing the effectiveness of the mobile admission process.This retrospective study was conducted at Chung-Ang University Gwangmyeong Hospital in South Korea (August 2022–January 2023). Turnaround times for the walk-in and mobile admission processes were compared. Patients were divided into mobile and walk-in groups based on their admission process. Collected timestamp data were extracted by examining patients' electronic medical record log time or caregivers' electronic signatures on consent forms. Time intervals between timestamp data were calculated and compared.We enrolled 4,344 patients to compare the turnaround time and demographics of the mobile (n = 1,336) and walk-in (n = 3,008) admission processes. The former had a significantly shorter mean turnaround time (13.4 minutes) than the latter (22.2 minutes). Female patients, younger patients, and those admitted to surgery departments were more likely to use the mobile process. Older patients were less likely to undergo mobile admissions. A linear regression analysis revealed that these factors significantly affected the usability of the mobile device admission process.Compared with the traditional walk-in admission process, the mobile admission process can reduce task completion time.
Keywords: hospital administration; patient admission; telemedicine; workflow